Contracting and gender equity in Tanzania: using a value chain approach to understand the role of gender in organic spice certification - Bullock, Renee; Gyau, A.; Mithoefer, D.; Swisher, M. (Cambridge University Press, 2018)
Value chain development (VCD) initiatives within the horticultural and organic sectors in Africa are promising strategies to improve smallholder welfare. Contracting institutional arrangements are a common feature of VCD initiatives and are increasing in number in sub-Saharan Africa as a way to source organic products from smallholder producers. The objective of this study is to better understand men and women’s participation in spice producing households that sell under contract and in conventional market chains in the East Usambaras, Tanzania. We draw on New Institutional Economics, political economy and the value chain analysis framework to assess the potential role of contracting to promote gender equity among smallholder organic horticultural producers. We describe intra-household decision making over resources and marketing, access to benefits of contracting, and labor distribution between men and women in contracting and non-contracting households. We then extend the gender analysis to evaluate the role of gender in contracting and conventional value chains operating within the community and district. Using a cross-sectional research design and data collected through 13 focus group discussions, 54 personal interviews and 156 household questionnaires, we show that contracting reduces transaction costs in the chain compared with the conventional trade. However, norms in the wider political economic context give rise to gendered patterns of participation in both household and chain activities in contracting and non-contracting households. Our findings suggest that contracting does not provide significant opportunities for women in married households to participate and benefit based on limited participation in decision-making and access to trainings. Divorced women and widows gain access to contract employment opportunities to earn income. This study highlights the importance of understanding gender relations in the household and community to guide the development of gender equitable VCD initiatives and contracting approaches.